PROPAGATION OF ELECTROMAGNETIC WAVES IN SOME PUBLIC BUILDINGS IN CROSS RIVER STATES, NIGERIA - Obot, E. P; Oku, D. E (European Scientific Journal, ESJ, 2014)
A Digital Community-Access (or Cable) Television (CATV) Analyzer with 24 channel spectrum 46 – 870MHz have been used to measured the received signal strength level, RxLev in four buildings (two office buildings and two residential buildings) in Calabar city at 519.25MHz. The results obtained indicated an average penetration loss of approximately 6dB with a standard deviation of 2dB. This is in accordance with several other studies done on this subject. In general, an increase has been found in the average signal strength when the receiver is moved upward in a building, the worst case situation being at ground floor.